The case book of Sherlock Holmes - Doyle, Arthur Conan; Abdalrhman, Ahmed (Cairo master publishing, 2023)
The case book of sherlock Holmes is the final set of twelve (out of a total fifty six) Sherlock Holmes shorts stories first published in the stand magazine between october 1921 and april 1927, the adventure of the illustrious client the adventure of the blanched soldier adventure of the mazer in stone the adventure of the three gables the adventure of the vsussex vampire the adventure of the three garridebs the problem of thor bridge the adventure of the creeping man the adventure of the lion's mane the adventure of the veiled lodger the adventure of shoscombe old place the adventure of the retired colourman
Keywords: Holmes, Sherlock -- Fiction; Detective and mystery stories, English; Private investigators -- England -- Fiction